Effect of Milk Source and Location on the Physicochemical Characteristics of White Cheese (Gibna bayda) - , Husna Eisa Ahmed Omer; , Mohamed Osman Mohamed Abdalla (Archives of Current Research International, 2017)
Aims: This study was conducted to evaluate the quality control of white cheese (Gibna bayda) processing in traditional plants. Methodology: White cheese was manufactured using raw cow milk from two areas in North Kordofan (Riash and Cazgail). Samples were collected from three stages (raw milk, curd after pressing and cheese delivered to market). Samples were collected in sterile plastic bags stored at 4°C in ice box and transported to the laboratory of Kordofan University for analysis. Raw milk and cheese were physicochemically (fat, protein, total solids, ash, pH) evaluated during processing stages. Results: The results showed that all chemical components were not significantly affected by the area in which cheese was made, except fat content which was higher (P<0.05) in cheese from Cazgail area (15.68%). During processing stages, fat and protein contents were significantly (P<0.001) higher in curd after pressing (16.68% and 14.16% respectively), while the other components (total solids, ash and pH) were not significantly affected by the stage of processing. Conclusion: There was no significant variation in physicochemical characteristics of cheese from different areas of milk collection and processing stages, and this indicates that the source of milk is the same for both regions in addition to processing conditions which did not show differences.